Reference‐Attached pH Nanosensor for Accurately Monitoring the Rapid Kinetics of Intracellular H+ Oscillations - Wen, Ming‐Yong; Qi, Yu‐Ting; Jiao, Yu‐Ting; Zhang, Xin‐Wei; Huang, Wei‐Hua (Small (Weinheim an der Bergstrasse, Germany), 2025)
Intracellular pH (pHi) is an essential indicator of cellular metabolic activity, as its transient or small shift can significantly impact cellular homeostasis and reflect the cellular events. Real‐time and precise tracking of these rapid pH changes within a single living cell is therefore important. However, achieving high dynamic response performance (subsecond) pH detection inside a living cell with high accuracy remains a challenge. Here a reference‐attached pH nanosensor (R‐pH‐nanosensor) with fast and precise pHi sensing performance is introduced. The nanosensor comprises a highly conductive H+‐sensitive IrRuOx nanowire (SiC@IrRuOx NW) as the intracellular working electrode and a SiC@Ag/AgCl NW as an intracellular reference electrode (RE) to diminish the interferences arising from cell membrane potential fluctuations. This whole‐inside‐cell detection mode ensures that the entire potential detection circuit is located within the same cell, and the R‐pH‐nanosensor is able to quantify the mild acidification of cytosol and completely record the fast pH variation within a single cell. It also enables real‐time potentiometric monitoring of the pHi oscillations, which synchronize with the glycolysis oscillations in cancer cells. Furthermore, the asymmetry in glycolysis oscillations wave is disclosed and the inhibitory effect of just lactate to glycolysis oscillations is further confirmed. A reference‐attached pH nanosensor is developed with the capability to timely and accurately monitor rapid intracellular pH variation. This nanosensor successfully tracks asymmetric pH fluctuations during glycolysis in cancer cells, reveals faster production of acidic metabolites over their removal, and clarifies the inhibitory effects of lactate rather than H+ to glycolysis.